THE RELATIONSHIP BETWEEN MOTIVATION AND PERFORMANCE OF IMPLEMENTING NURSES IN PROVIDING NURSING CARE AT TUAN RONDAHAIM REGIONAL HOSPITAL PAMATANG RAYA SIMALUNGUN REGENCY - Ibnu Fajar; Tresia Melianna Simanjuntak; Yeci Theresia Simanjuntak (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Motivation based on Maslow's theory of needs consists of physiological needs, a sense of security, belonging, self-esteem and self-actualization. Nurse performance starts from assessment, diagnosis, planning, implementation and evaluation. This study aims to determine the relationship between motivation and the performance of implementing nurses in providing nursing care at the Tuan Rondahaim Pamatang Raya Regional General Hospital (RSUD), Simalungun Regency. This research method is descriptive correlative, where the population of inpatient nurses is 35 people, the sampling technique is done by total sampling. Data collection was carried out in May 2014 using a questionnaire consisting of three parts, namely the first on demographic data, the second part on the motivational questionnaire and the third part in the form of nurse performance observation sheets. There was almost no difference in the motivation and performance of the implementing nurses where the percentage of good motivation was 48.6% and bad motivation was 51.4%. The majority of practicing nurses had a good performance of 57.1% even though there were 42.9% of nurses whose performance was not good. The results of the study showed that there was a relationship between motivation and the performance of implementing nurses with a value of p = 0.006 <0.05. Further research is suggested to pay more attention to data collection methods so that the data obtained is more accurate and representative. The results of the study showed that there was a relationship between motivation and the performance of implementing nurses with a value of p = 0.006 <0.05. Further research is suggested to pay more attention to data collection methods so that the data obtained is more accurate and representative. The results of the study showed that there was a relationship between motivation and the performance of implementing nurses with a value of p = 0.006 <0.05. Further research is suggested to pay more attention to data collection methods so that the data obtained is more accurate and representative.